Small Posterior Cranial Fossa and Cerebellopontine Cistern Volumes Are Associated With Bilateral Trigeminal Neuralgia - Liu, Jiayu; Liu, Ruen; Liu, Bo; Zhou, Jingru; Fan, Cungang; Jiao, Feng; Wang, Dongliang; Li, Fang; Hei, Bo (Frontiers in Neurology, 2020)
Objective: To investigate whether small volumes of the posterior cranial fossa and cerebellopontine cisterns are associated with bilateral trigeminal neuralgia (BTN) and to provide further knowledge regarding the etiology and treatment of this rare disease. Methods: We retrospectively analyzed clinical data and imaging examination results for 30 BTN patients between January 2009 and December 2019. Thirty age- and sex-matched healthy individuals and 30 patients with unilateral trigeminal neuralgia (UTN) were selected as two control groups. The volume of the posterior cranial fossa (VPCF) and volumes of the cerebellopontine cisterns were measured using ITK-SNAP 3.0, which considers the cerebrospinal fluid (CSF) volume based on the region of interest (ROI). Preoperative and postoperative statuses were based on visual analog scale (VAS) pain scores and Barrow Neurological Institute (BNI) scores. Results: A total of 30 patients (11 males; 19 females) were included, and the age of the BTN participants ranged from 41 to 77 (59.93 ± 9.89) years. The duration of TN ranged from 1 to 20 (5.36 ± 3.92) years, and the interval between the two sides ranged from 0 to 3 (1.10 ± 0.79) years. Three patients (10%) in the BTN group had familial trigeminal neuralgia, with no other hereditary history of neurological disorders. In BTN patients, with 25 (83.3%) cases on the left side and 26 (86.7%) on the right side, veins were identified in the operative field and regarded as the individual or offending vessel. The mean VPCF was significantly lower in the patients with BTN than in the healthy controls (4,813 ± 1,155 mm3 vs. 5,127 ± 1,129 mm3, p = 0.008). The volumes of the cerebellopontine cisterns on both sides were significantly smaller in the BTN patients than in the healthy controls (477 ± 115 mm3 vs. 515 ± 112 mm3 on the left side, p = 0.001; and 481 ± 114 mm3 vs. 515 ± 110 mm3 on the right side, p = 0.007). There was no significant difference between the BTN group and the UTN group in terms of the VPCF (4,843 ± 1,184 mm3 vs. 4,813 ± 1,155 mm3, p = 0.402), and there was also no significant difference between the two groups in terms of preoperative VAS pain scores or BNI scores. Conclusion: Overcrowding in the posterior fossa will lead to closer neurovascular relations and, a higher incidence of NVC, and ultimately may be more likely to lead to TN. Veins are the common offending vessels that cause BTN; they might be associated with abnormal vascular development leading to NVC. Microsurgical vascular decompression (MVD) is a safe and effective method for the treatment of BTN, similar to UTN.